Protein kinase C iota facilitates insulin‐induced glucose transport by phosphorylation of soluble nSF attachment protein receptor regulator (SNARE) double C2 domain protein b. Issue 3 (1st December 2018) - Nomiyama, Ryuta; Emoto, Masahiro; Fukuda, Naofumi; Matsui, Kumiko; Kondo, Manabu; Sakane, Ayuko; Sasaki, Takuya; Tanizawa, Yukio
Abstract: Aims/introduction: Double C2 domain protein b (DOC2b), one of the synaptotagmins, has been shown to translocate to the plasma membrane, and to initiate membrane‐fusion processes of vesicles containing glucose transporter 4 proteins on insulin stimulation. However, the mechanism by which DOC2b is regulated remains unclear. Herein, we identified the upstream regulatory factors of DOC2b in insulin signal transduction. We also examined the role of DOC2b on systemic homeostasis using DOC2b knockout (KO) mice. Materials and Methods: We first identified DOC2b binding proteins by immunoprecipitation and mutagenesis experiments. Then, DOC2b KO mice were generated by disrupting the first exon of the DOC2b gene. In addition to the histological examination, glucose metabolism was assessed by measuring parameters on glucose/insulin tolerance tests. Insulin‐stimulated glucose uptake was also measured using isolated soleus muscle and epididymal adipose tissue. Results: We identified an isoform of atypical protein kinase C (protein kinase C iota) that can bind to DOC2b and phosphorylates one of the serine residues of DOC2b (S34). This phosphorylation is essential for DOC2b translocation. DOC2b KO mice showed insulin resistance and impaired oral glucose tolerance on insulin and glucose tolerance tests, respectively. Insulin‐stimulated glucose uptake was impaired in isolated soleus muscle and epididymal adipose tissues from DOC2b KO mice. Conclusions: We propose a novel insulin signaling mechanism by which protein kinase C iota phosphorylates DOC2b, leading to glucose transporter 4 vesicle translocation, fusion and facilitation of glucose uptake in response to insulin. The present results also showed DOC2b to play important roles in systemic glucose homeostasis. Abstract : Protein kinase C iota phosphorylates double C2 domain protein b, leading to glucose transporter 4 vesicle translocation, fusion and facilitation of glucose uptake in response to insulin. A kinase deficient mutant (KD) of protein kinase C iota inhibited double C2 domain protein b translocation on insulin stimulation.